(0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

-(x, 0) → x
-(0, s(y)) → 0
-(s(x), s(y)) → -(x, y)
lt(x, 0) → false
lt(0, s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0) → 0
div(0, y) → 0
div(s(x), s(y)) → if(lt(x, y), 0, s(div(-(x, y), s(y))))

Rewrite Strategy: FULL

(1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
-(s(x), s(y)) →+ -(x, y)
gives rise to a decreasing loop by considering the right hand sides subterm at position [].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

(3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

(4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

S is empty.
Rewrite Strategy: FULL

Infered types.

(6) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

(7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
-, lt, div

They will be analysed ascendingly in the following order:
- < div
lt < div

(8) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
-, lt, div

They will be analysed ascendingly in the following order:
- < div
lt < div

(9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)

Induction Base:
-(gen_0':s3_0(0), gen_0':s3_0(0)) →RΩ(1)
gen_0':s3_0(0)

Induction Step:
-(gen_0':s3_0(+(n5_0, 1)), gen_0':s3_0(+(n5_0, 1))) →RΩ(1)
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) →IH
gen_0':s3_0(0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

(11) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

Lemmas:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
lt, div

They will be analysed ascendingly in the following order:
lt < div

(12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
lt(gen_0':s3_0(n393_0), gen_0':s3_0(n393_0)) → false, rt ∈ Ω(1 + n3930)

Induction Base:
lt(gen_0':s3_0(0), gen_0':s3_0(0)) →RΩ(1)
false

Induction Step:
lt(gen_0':s3_0(+(n393_0, 1)), gen_0':s3_0(+(n393_0, 1))) →RΩ(1)
lt(gen_0':s3_0(n393_0), gen_0':s3_0(n393_0)) →IH
false

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

(14) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

Lemmas:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)
lt(gen_0':s3_0(n393_0), gen_0':s3_0(n393_0)) → false, rt ∈ Ω(1 + n3930)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
div

(15) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol div.

(16) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

Lemmas:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)
lt(gen_0':s3_0(n393_0), gen_0':s3_0(n393_0)) → false, rt ∈ Ω(1 + n3930)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

(17) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)

(19) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

Lemmas:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)
lt(gen_0':s3_0(n393_0), gen_0':s3_0(n393_0)) → false, rt ∈ Ω(1 + n3930)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

(20) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)

(22) Obligation:

TRS:
Rules:
-(x, 0') → x
-(0', s(y)) → 0'
-(s(x), s(y)) → -(x, y)
lt(x, 0') → false
lt(0', s(y)) → true
lt(s(x), s(y)) → lt(x, y)
if(true, x, y) → x
if(false, x, y) → y
div(x, 0') → 0'
div(0', y) → 0'
div(s(x), s(y)) → if(lt(x, y), 0', s(div(-(x, y), s(y))))

Types:
- :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → false:true
false :: false:true
true :: false:true
if :: false:true → 0':s → 0':s → 0':s
div :: 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_false:true2_0 :: false:true
gen_0':s3_0 :: Nat → 0':s

Lemmas:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

(23) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n50)